Characterisation of a Complex CaZr0.9Ce0.1Ti2O7 Glass–Ceramic Produced by Hot Isostatic Pressing - Malin C. J. Dixon Wilkins; Clémence Gausse; Luke T. Townsend; Laura J. Gardner; Claire L. Corkhill (Ceramics, 2022)
The behaviour of Ce-containing zirconolites in hot isostatically pressed (HIPed) materials is complex, characterised by redox interactions between the metallic HIP canister that result in reduction of Ce4+ to Ce3+. In this work, a glass–ceramic of composition 70 wt.% CaZr0.9Ce0.1Ti2O7 ceramic in 30 wt.% Na2Al2Si6O16 glass was produced by HIP (approx. 170 cm3 canister) to examine the extent of the material–canister interaction. A complex material with six distinct regions was produced, with the extent of Ce reduction varying depending on the distance from the canister. Notably, the innermost bulk regions (those approximately 7 mm from the canister) contained only Ce4+, demonstrating that a production-scale HIPed glass–ceramic would indeed have a bulk region unaffected by the reducing environment induced by a ferrous HIP canister despite the flow of glass at the HIP temperature. Each of the six regions was characterised by XRD (including Rietveld method refinements), SEM/EDX and linear combination fitting of Ce L3-edge XANES spectra. Regions in the lower part of the canister were found to contain a significantly higher fraction of Ce4+ compared to the upper regions. Though zirconolite-2M was the major crystalline phase observed in all regions, the relative abundances of minor phases (including sphene, baddeleyite, rutile and perovskite) were higher in the outermost regions, which comprised a significantly reduced Ce inventory.